Rinosporidiose nasal em equino no Sul do Rio Grande do Sul, Brasil - Relato de caso - Bernardo, Fábio Darlan; Pazinato, Fernanda Maria; Alves, Carlos Eduardo Fonseca [UNESP]; La Cruz Bueno, Verônica; Franciscato, Carina; Elias, Fabiana (My University, 2016)
Rhinosporidiosis is a chronic infection characterized by the growth of polypoid structures in mucous membranes. The etiologic agent is Rinosporidium seeberi currently recognized as a protist parasite. It is suspected to be a water saprophyte which allows transmission through contact with contaminated water or even through inhalation, and this means mainly associated with human infection. Considering few cases described in Brazil and the need to better understand the epidemiology The aim of this study is to report a case of rhinosporidiosis on a horse two years. The animal, from the city of Pelotas, was treated at the Veterinary Clinical Hospital of the Universidade Federal de Pelotas, Rio Grande do Sul, where demonstrated sneezing and serous bilateral nasal discharge. Medial septal region in the left nostril there was the presence of granulomatous nodules polypoid with about three cm in diameter. The same friable consistency and reddish with small whitish granules. Since clinical parameters and blood counts were within the reference values for the species; and changes in airway endoscopy not were observed. Carried out surgical excision of the tumor mass by injecting local anesthesia and general anesthesia, dorsal buccal branch of the facial nerve. The procedure was performed with Allis clamp and scalpel aid and subsequent cauterization of the implantation base with liquid nitrogen. Mass of the fragments were immersed in 10% formalin for histopathology. Approximately 15 days after the procedure, the surgical wound had completely healed. Histologically there was numerous structures compatible with sporangia R. seeberi in different stages of maturation, amid immature connective tissue and intense inflammation where macrophages and polymorphonuclear predominant cells (neutrophils and eosinophils). The lesion formed by inflammatory response against the parasite, said clinical signs demonstrated by the horse due to partial obstruction of air flow and mucosal irritation. Alre-ady the whitish granules observed in macroscopic match agent sporangia. The clinical, macroscopic and histological findings were similar to other reports, but have been found cases with more severe clinical course including difficulty breathing and involvement of the lower anatomical structures of the respiratory system, such as larynx. Surgical resection of the mass has excellent results and excellent prognosis; however, there may be late relapses requiring prolonged follow-up. This was the second case of the disease diagnosed in the same neighborhood of the city. This leads to suspect source of infection at the site and reinforces the need to investigate the agent's presence in the environment, such as spore detection in stagnant water, as well as conduct seroepidemiological studies; thus contributing to the understanding of the epidemiology, still not very clear, this disease. In conclusion, clinical signs, pathology and viewing of R. seeberi sporangia were enough to confirm the diagnosis. In addition, it must include the rhinosporidiosis the differential diagnosis of other diseases of the respiratory system of horses in the southern region of the State.
Equine nasal rhinosporidiosis in the Southern Rio Grande do Sul, Brazil - Case report
Keywords: Epidemiology; Equus caballus; Histopathology; Rhinosporidium seeberi; Surgical excision